2001
DOI: 10.1046/j.1365-2672.2001.01215.x
|View full text |Cite
|
Sign up to set email alerts
|

The growth of Bacillus stearothermophilus on stainless steel

Abstract: Aims: To determine the potential for Bacillus stearothermophilus cells to form bio®lms of signi®cance in dairy manufacture. Methods and Results: The ability of isolates of B. stearothermophilus from dairy manufacturing plants to attach to stainless steel surfaces was demonstrated by exposing stainless steel samples to suspensions of spores or vegetative cells and determining the numbers attaching using impedance microbiology. Spores attached more readily than vegetative cells. The attachment of cells to stainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
78
0
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(87 citation statements)
references
References 6 publications
5
78
0
4
Order By: Relevance
“…3). Previous studies have shown that exponentially grown cells are less adhesive (14,36,41). Furthermore, there is a bondaging or rigidification of the viscoelastic properties of the binding of exponentially grown cells to surfaces, probably due to an increase in CSH with time as the cells starve (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…3). Previous studies have shown that exponentially grown cells are less adhesive (14,36,41). Furthermore, there is a bondaging or rigidification of the viscoelastic properties of the binding of exponentially grown cells to surfaces, probably due to an increase in CSH with time as the cells starve (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…Biofilms are formed when spores present in the raw milk survive pasteurization, adhere to stainless steel surfaces, and germinate when and where conditions are suitable. As the biofilm matures, cells and spores can slough off and contaminate the product flowing past (13). Spore concentrations as high as 10 5 spores g Ϫ1 can occur in milk powder, resulting in it being downgraded to a lower-value product.…”
mentioning
confidence: 99%
“…Yersinia enterocolitica, Salmonella thyphimurium, (HOOD, 1996;LEJEUNE, 2003), Listeria monocytogenes (BERESFORD et al, 2001;LEJEUNE, 2003), Escherichia coli, Staphylococcus aureus ( POMPERMAYER; LEREBOUR et al, 2004), Vibrio parahaemolyticus (WONG et al, 2002), and Klebsiella pneumoniae (DI MARTINO et al, 2003) are included among pathogenic bacteria. Spores of Bacillus cereus (FAILLE et al 2001;JULLIEN et al, 2002), Bacillus stearothermophilus (FLINT et al, 2001), and Bacillus sporothermodurans (AKUTSU, 2001) are also involved in adherence processes and biofilm formation.…”
Section: Introductionmentioning
confidence: 99%